On strongly h-convex stochastic processes - Alawiah Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2020)
In this paper, the concept of strongly h-convex stochastic processes is introduced. New inequality related to Hermite-Hadamard type for strongly h-convex stochastic processes is obtained. Some properties of convex stochastic processes are presented. The results given in this work are generalizations of the known results.